ANALISIS EFEKTIVITAS KERJA PEGAWAI PADA BAGIAN REGU UNIT LAKA LANTAS POLRES PURWOREJO (STIE Rajawali Purworejo, 2018)
The purpose of this study is to determine the effectiveness of employee workon the Unit Unit Laka Lantas Purworejo Police. Sampling using the census method, which takes all the population as sempel as many as 6 employees. This research uses Likert-scale data analysis method.Based on the research that the authors do ultimately obtained results for the variable motivation 76%, job satisfaction 91%, 58% workload variable and time variable completing 78% task. Of the four variables the most dominant variable is job satisfaction variable with a score of 55 or 91%. While the lowest variable is the workload variable with a score of 35 or 58% cause factor is due to the unbalanced amount between the workload with the number of personnel available. Leaders must have a policy to increase incentives and bonuses and increase the number of personnel for the team of Laka Unit Purworejo Police to have a balance between the number of personnel with the work load run by laka unit team in order to run the task and finish the work can be more optimal with good results or satisfying and in serving the community can be better, proportional and professional.